POLA KOMUNIKASI SOSIAL PASCA AKSI BELA ISLAM SERTA IMPLIKASINYA TERHADAP ORMAS ISLAM DI INDONESIA (Analisis Interaksi Antar Ormas Islam di Masjid Thoriqul Huda Kelurahan Rahma) - ADE IRWANSYAH (Jurnal khabar: Komunikasi dan Penyiaran Islam, 2020)
In principle, the purpose of this study is to find out the social communication patterns of Muslim communities after Islamic defense actions held at Monas lately. Therefore, in this study using several aspects of research such as observation, interviews to documentation, especially social geographical communities in the Rahmah Lubuklinggau village